Coupled Effects of Particle Shape and Grain-Scale Deformability on Repose Angle of Sand-Rubber Granule Mixture - Ari, Abdulmuttalip; Akbulut, Suat (ASCE-AMER SOC CIVIL ENGINEERS, 2024)
Particle shape and grain-scale deformability play key roles in controlling the response of granular material; however, in the literature, the effects of these parameters have generally been evaluated separately. In this context, this study attempts to investigate the coupled effects of these parameters on the repose angle of the sand-rubber mixture using the discrete-element method. For this purpose, the realistic shapes of three different sands and two different rubbers were reflected in the simulations. The grain-scale deformability of rubber particles was modeled by connecting the ball-cluster structure with the linear parallel bond contact model. In addition, to clearly distinguish the role of deformability in the response, the rubber particles were simulated also using a rigid clump model. The parameters of the model were validated using different tests for grain and sample scales. A series of numerical analyses were conducted, and repose angles were determined using image processing techniques. The variation of repose angle was correlated with porosity in the sample scale. The contribution of interparticle friction and interlocking mechanism on the repose angle was revealed using the coordination number and anisotropy coefficient of the contacts in the microscale. The results show that the angle of repose increases with increasing irregularity of the particles. Even though the interlocking mechanism is weakened by the addition of soft rubber, there is an increase in the repose angle of the mixtures thanks to the superior interparticle friction properties of the rubber particles. The results indicate that a high repose angle can be constituted by controlling the particle shape and deformability parameters.
Keywords: Particle shape; Angle of repose; Particle deformability; Sand; Rubber; Discrete-element method; SHEAR-STRENGTH; PLANE-STRAIN; BEHAVIOR; MICRO; SIMULATIONS; ASSEMBLIES; MORPHOLOGY; STIFFNESS; IMAGE; STATE; Engineering